Electrodeposited nickel cobalt manganese based mixed sulfide nanosheets for high performance supercapacitor application - Sahoo, S.; Mondal, R.; Late, D. J.; Rout, C. S. (Microporous and Mesoporous Materials, 2017)
Porous multi component Nickel Cobalt Manganese Sulfide (NCMS) nanosheets have been grown on Ni foam by cathodic electrodeposition method. The as-prepared NCMS nanosheets sample is used as an electrode material for supercapacitor application due to its large electrochemically active surface and high porosity structure. Moreover, NCMS nanosheets have good electrical and mechanical connections to the conductive Ni foam to achieve enhanced reaction kinetics with improved electrode integrity. The NCMS nanosheets exhibit an ultrahigh specific capacitance of 2717 Fig at a current density of 1 Aug with excellent cyclic stability and energy density of 94.07 Wh/kg. The electrodeposited NCMS nanosheets with extraordinary electrochemical performance enable the novel electrodes to hold great potential for high efficient energy storage systems.